The ‘hierarchy of victims’ in Northern Ireland: a framework for critical analysis - Jankowitz, Sarah E. (International journal of transitional justice, 2018)
Acknowledging and addressing victims’ experiences is a central objective of transitional justice (TJ) processes, but the disparate narratives of victimhood inherent in conflict complicate this task. In Northern Ireland, contention over who can be recognized and prioritized as a victim is exemplified in the so-called ‘hierarchy of victims.’ In an effort to advance a more critical commentary on victimhood in TJ, this article offers a nuanced analysis of hierarchy by developing an original framework that illuminates the distinct meanings and functions of hierarchy in transitional contexts. Four distinct yet overlapping ‘types’ of hierarchy are identified through empirical analysis: moral hierarchies, hierarchies of attention, pragmatic hierarchies and intergroup hierarchies. The pragmatic hierarchy emerges as the most appropriate for shaping TJ policy. Most problematic is the intergroup hierarchy, which intersects with other hierarchies to reinforce conflicting narratives of legitimate violence, victimhood and responsibility.